Capital Intensity dan Tax Avoidance Dengan Leverage Sebagai Variabel Moderasi - Dwi Sumba Wirawan, I Made (Fakultas Ekonomi Universitas Gresik, 2023)
Taxes are the main source of input for state revenue. Thus, the government appealed to the public to obey in paying taxes. However, businesspeople consider taxes as a burden, so company management tries to avoid the tax burden. This study examines the effect of capital intensity on tax avoidance. In addition, this study also examines the ability of leverage as a moderating variable. The number of samples analyzed was 155 samples in the form of financial reports from manufacturing companies listed on the Indonesia Stock Exchange. The sampling technique in this study is the non-probability sampling method with a purposive sampling technique with the criteria of companies (issuers) that have issued consecutive financial reports for the 2017-2021 period, the company has not suffered losses during that period, and the company uses the rupiah value unit in its financial reports. The analysis technique used is simple linear regression and Moderated Regression Analysis (MRA). The results of the analysis show that capital intensity has no effect on tax availability. Leverage weakens the effect of capital intensity on tax avoidance